One-year real-life outcomes of lanadelumab therapy in Romanian patients with hereditary angioedema due to C1-inhibitor deficiency - Bara, Noémi Anna; Nădășan, Valentin; Deleanu, Diana (Frontiers in Allergy, 2025)
IntroductionIn the majority of patients with hereditary angioedema (HAE) due to C1-inhibitor deficiency (HAE-C1INH), effective long-term prophylactic (LTP) treatment can achieve complete disease control. Lanadelumab is one of the first-line option recommended for this purpose. Our study aimed to evaluate changes in disease control, quality of life, and attack frequency among Romanian HAE-C1INH patients, during the first year of treatment with lanadelumab. MethodsThis non-interventional prospective study included the Romanian HAE-C1INH patients enrolled in the first year of the national lanadelumab treatment program. Angioedema Control Test, (AECT), Angioedema Quality of Life Questionnaire (AE-QoL) and attacks frequency were recorded at baseline and at 3, 6, 9 and 12 months.ResultsTwenty-four patients (14 women [58.3%], 10 men [41.7%]) initiated lanadelumab therapy, with a mean age of 40.7 years. Most had HAE-C1INH type I (22 patients, 91.7%), and one patient was under 18 years of age. Ten patients switched from LTP with intravenous plasma-derived C1-INH, while 14 were previously managed with on-demand therapy only. Baseline scores were: AECT 4.5 [interquartile range (IQR) 2.0], AE-QoL 66.1 [standard deviation (SD) 18.3], and a mean attack frequency of 10.0 (IQR 4.0) (over the preceding three months). Improvements were observed at each follow-up point, with respective scores at 3, 6, 9 and 12 months as follows: three months: AECT 12.0 (IQR 5.8) / AE-QoL 35.3 (SD 23.2)/ attacks 3.4 (IQR 5.0); six months: AECT 12.3 (IQR 5.3) / AE-QoL 35.4 (SD 25.4)/ attacks 2.8 (IQR 4.8); nine months: AECT 12.6 (IQR 5.8) / AE-QoL 34.1 (SD 23.2)/ attacks 2.2 (IQR 3.8) and 12 months: AECT 12.9 (IQR 5.5) / AE-QoL 32.1 (SD 21.6) / attacks 1.4 (IQR 2.0). Seven patients became symptom-free after the first dose, and four more achieved this status within the first three months. DiscussionLTP with lanadelumab provided effective disease control and significantly improved quality of life in patients with HAE-C1INH over the course of one year. Regular evaluations at relatively short intervals by the availability and ease of administration of validated questionnaires serve as a useful tool for clinicians in the comprehensive assessment of HAE patients and offer a valuable means of monitoring treatment effectiveness.